THE EFFECTIVENESS OF THE USE OF THE BIOLOGICAL PREPARATION "IVAN OVSINSKY-FULVOGUMAT" OF THE BUKHARA-6 VARIETY OF COTTON IN THE CONDITIONS OF THE BUKHARA REGION - Akhmedov , Muhammad; Karimova, Khalida; Sharipov, Odiljon (Innovatsion texnologiyalar, 2024)
A lack of organic matter in the top layer of soil leads to a sharp decrease in the number of beneficial microorganisms. In recent years, it has been noted that Fusarium wilt affects varieties grown in all regions of the country. In an experiment conducted in the Bukhara region. Presowing treatment of cotton seeds with preparations Ivan Ovsinsky - fulvohumate and spraying in the phase of 2-3 true leaves and the budding phase had a certain positive effect on the incidence of plants with Fusarium wilt. On irrigated meadow-alluvial soils, due to the use of fulvohumate "Ivan Ovsinsky", the resistance of cotton to various diseases increased and the agrochemical properties of the soil improved, and an additional yield of 2.3-3.5 c/ha of cotton was obtained. Farm profitability increased from 15.9% to 21.4%, respectively. It is recommended to use this preparation on meadowalluvial soils of the Bukhara oasis